2002
DOI: 10.1523/jneurosci.22-18-07892.2002
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Synaptic Plasticity Genes during Consolidation of Fear Conditioning

Abstract: In mammals, long-term memory induced by Pavlovian fear conditioning has been shown to be dependent on the amygdala during a protein and mRNA synthesis-dependent phase of memory consolidation. We have used genes identified in a kainic acid model of synaptic plasticity as in situ hybridization probes during the consolidation period after fear conditioning. We found that these genes were transcriptionally regulated in several brain areas only when stimuli were presented in a manner that supported behavioral learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
148
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(159 citation statements)
references
References 60 publications
11
148
0
Order By: Relevance
“…158 In our latest study we replicated the acquisition finding, reporting a decrease in gephyrin protein and the surface expression of GABA A receptors 2 and 6 h after fear acquisition, respectively. Following extinction training, gephyrin mRNA, gephyrin protein and GABA A receptor binding increased at 2, 4 and 6 h, respectively.…”
Section: Neurotransmitter Systemssupporting
confidence: 69%
“…158 In our latest study we replicated the acquisition finding, reporting a decrease in gephyrin protein and the surface expression of GABA A receptors 2 and 6 h after fear acquisition, respectively. Following extinction training, gephyrin mRNA, gephyrin protein and GABA A receptor binding increased at 2, 4 and 6 h, respectively.…”
Section: Neurotransmitter Systemssupporting
confidence: 69%
“…Aversive stimulation has been shown to induce a second stage of protein synthesis that reaches a significantly increased level 4-8 h after stimulus presentation (Grecksch and Matthies 1980;Freeman et al 1995;Quevedo et al 1999;Ressler et al 2002). Therefore, we administered ANI at 3, 6, and 18 h after sampling.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the search for the molecular constituents of such a "memory trace" in the brain, the behavioral tasks used have focused on associative learning (e.g., fear conditioning and avoidance learning). Under certain conditions it has also been reported that two or more stages of protein synthesis are involved in memory consolidation (Grecksch and Matthies 1980;Freeman et al 1995;Quevedo et al 1999;Ressler et al 2002). However, classical (fear) conditioning and avoidance learning require negative reinforcement.…”
mentioning
confidence: 99%
“…Electrophysiological and c-fos immunoreactivity studies in rodents have indeed demonstrated that the habenula is activated in response to various aversive stressors, including stimulation of the tail, restraint, novel environments, and footshock (Benabid and Jeaugey, 1989;Wirtshafter et al, 1994;Gao et al, 1996;Smith et al, 1997). We have previously reported that the habenula also showed increased expression of synaptic plasticity genes associated with long-term changes in neuronal activity in response to stress associated with fear conditioning (Ressler et al, 2002). Along with evidence indicating the habenula's role in regulating monoamine transmission, these results suggest that stress may induce long-term structural changes in the habenula which influences subsequent monoamine-dependent behaviors.…”
Section: Introductionmentioning
confidence: 95%